2013
DOI: 10.1186/2193-1801-2-631
|View full text |Cite
|
Sign up to set email alerts
|

Cropping practices, soil properties, pedotransfer functions and organic carbon storage at Kuanria canal command area in India

Abstract: Effects of cropping practices on soil properties viz. particle size distribution, pH, bulk density (BD), field capacity (FC, -33 kPa), permanent wilting point (PWP, -1500 kPa), available water capacity (AWC) and soil organic carbon (SOC) were assessed. The pedotransfer functions (PTFs) were developed for saturated hydraulic conductivity (Ks), water retention at FC and PWP of soils for different sites under major cropping system in a canal irrigated area. The results revealed that the soils are mainly composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Moreover, SOC acts as a binding agent that improves the moisture absorption capacity of the soil [70]. These findings agree with earlier studies that reported that silt, clay, and SOC are significantly and positively correlated to both FC and PWP [16,17,21,42,71,72]. The findings of this study suggest that sand, silt, clay, and SOC content can be used as the explanatory variables in the estimation of soil moisture content at both FC and PWP.…”
Section: Correlation Analysissupporting
confidence: 91%
“…Moreover, SOC acts as a binding agent that improves the moisture absorption capacity of the soil [70]. These findings agree with earlier studies that reported that silt, clay, and SOC are significantly and positively correlated to both FC and PWP [16,17,21,42,71,72]. The findings of this study suggest that sand, silt, clay, and SOC content can be used as the explanatory variables in the estimation of soil moisture content at both FC and PWP.…”
Section: Correlation Analysissupporting
confidence: 91%
“…The normal annual rainfall is about 592 mm spread over 23 days. The rainfall occurs during the southwest monsoon and about 1,500 mm annual evaporation under Ustic soil moisture regime (Mandal et al, ). The southwest monsoon contributes about 84% of the annual rainfall (499 mm) with July and August being the wettest months (Central ground water board, Ministry of water resources, Government of India, ).…”
Section: Methodsmentioning
confidence: 99%
“…Higher BD in agricultural soils is due to machinery traffic during cultivation which led to soil compaction, one of the significant challenges in agricultural fields in several parts of the world [71,74,75]. Higher BD values in the cultivated land and lower values in natural forest land can be related to the level of soil organic matter.…”
Section: Bulk Density (Bd)mentioning
confidence: 99%
“…This was confirmed by the significant correlation (r = 0.81; p < 0.01) between K sat and SOM (Figure 4a). Lower K sat in cultivated soils (RA and IC) could be due to the use of heavy machinery which can affect the continuity of macropores within the topsoil, reduce aggregate stability, and cause soil compaction leading to reduction in the ability of the soil to transmit water from soil surface to below ground [71,74,75,87]. In cultivated soils, K sat can also be reduced due to the compounding effects of rainfall and surface runoff in the absence of vegetation cover [88].…”
Section: Saturated Hydraulic Conductivity (Ksat)mentioning
confidence: 99%